Sewage sludge minimisation by means of wet oxidation: process performance and economic sustainability. (1st January 2014) - Bertanza, Giorgio; Zanaboni, Sabrina; Canato, Matteo; Laera, Giuseppe; Galessi, Raniero
Today, several technologies and management strategies are proposed and applied in WWTPs to minimise sludge production and contamination and their techno-economic feasibility has to be carefully evaluated. In this work (which is being conducted within the European Union project 'ROUTES'), based on bench results, a mass balance was drawn for a WWTP (500, 000 PE), where it was supposed to install a wet oxidation (WO) stage for sludge minimisation. The design of treatment units and the estimation of capital and operation costs were then performed. Subsequently, a procedure for technical-economic assessment was developed. Basically, this procedure consists in the definition and ranking of several technical (e.g., reliability of the technology, complexity and integration with the existing facilities, amount of residues to be disposed of or recovered, etc.) and economic aspects. Preliminary results have shown WO to be a suitable solution for sludge minimisation.